2015
DOI: 10.1155/2015/807683
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Serum Growth Differentiation Factor-15 Level in Patients with Obstructive Sleep Apnea

Abstract: Purpose. Growth differentiation factor-(GDF-) is a prognostic biomarker in cardiovascular disorders (CVD). GDF-15 level was not studied in patients with obstructive sleep apnea syndrome (OSAS) before. In this study, we investigated serum GDF-15 levels in OSAS patients and compared them with healthy controls. Material and Methods. Polysomnographically, confirmed forty consecutive OSAS patients (20 men and 20 women) and forty consecutive healthy controls (23 men and 17 women) were enrolled in the study. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…In our results, interestingly, it was revealed that there is no significant relationship between OSAS severities and GDF-15. However, studies on GDF-15 have found it associated with many chronic diseases (8)(9)(10)(11)(12)(13)(14). Studies have more clearly demonstrated the relationship between cardiac pathologies and GDF-15 (5,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our results, interestingly, it was revealed that there is no significant relationship between OSAS severities and GDF-15. However, studies on GDF-15 have found it associated with many chronic diseases (8)(9)(10)(11)(12)(13)(14). Studies have more clearly demonstrated the relationship between cardiac pathologies and GDF-15 (5,12).…”
Section: Discussionmentioning
confidence: 99%
“…A study where OSAS patients were compared to a control group did not find a GDF-related difference. However, in the study, the OSAS group was assessed without separation into sub-groups based on severity (mild-moderate-severe) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Отмечена отрицательная корреляция уровня GDF-15 с ФВ ЛЖ (R=-0,29; p=0,04). Созвучные результаты демонстрируют и другие исследователи, описывая в ряде клинических работ связь уровня GDF-15 с факторами риска ФП (ожирение, СД, возраст, атеросклероз, АГ, ХСН, ренальная дисфункция, степень фиброза ЛП) [18][19][20][21][22][23][24]. В данном Для изучения признаков, способных влиять на клиническое течение ФП в виде ее рецидивирования, были проведены однофакторный и многофакторный регрессионные анализы Кокса.…”
Section: результаты и обсуждениеunclassified
“…Существуют исследования, демонстрирующие ассоциацию уровня GDF-15 с площадью фиброза левого предсердия, индексом объема левого предсердия, уровнем N-концевого фрагмента мозгового натрийуретического пептида при ФП [19,20]. Данные о содержании GDF-15 в крови пациентов с СОАС скудны: в доступной научной литературе приведено лишь исследование Kamran S. и соавт., где не было обнаружено статистически значимых различий по уровню GDF-15 у пациентов с наличием СОАС и у пациентов без данного синдрома [21]. В связи с вышеизложенным определенный интерес представляет вопрос о том, сопровождается ли сочетание ФП и СОАС изменениями содержания GDF-15, а также эффективен ли GDF-15 как прогностический биомаркер рецидива ФП в данной субпопуляции пациентов.…”
Section: Introductionunclassified
“…Interestingly, overexpressed GDF15 is able to extend animal lifespan [ 14 ]. Only one study investigated GDF15 in relation to sleep disorders, and reported no correlation between GDF15 serum levels and Obstructive Sleep Apnea Syndrome (OSAS) [ 15 ]. HN is a mitochondrial DNA-encoded peptide endowed with cytoprotective and anti-apoptotic effects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%